Efficacy of a Single-Task ERP Measure to Evaluate Cognitive Workload During a Novel Exergame - Ghani, Usman; Signal, Nada; Niazi, Imran Khan; Taylor, Denise (Frontiers in Human Neuroscience, 2021)
This study aimed to validate the efficacy of single-task event-related potential (ERP) measures of cognitive workload to be implemented in exergame-based rehabilitation settings. Twenty-four healthy participants took part in a novel gamified balance task where task-irrelevant auditory tones were presented in the background to generate ERPs in the participants’ electroencephalogram (EEG). For the balance task, a computer-based tilt-ball game was combined with a balance board. Participants played the game by tilting the balance board with weight shifts, which moved a ball to score goals. The game difficulty was varied (easy, medium, and hard) by adjusting the size of the goalposts. Goals scored and participant’s ratings were used as a measure of perceived task difficulty. Participants experienced a significant difference in the three levels of task difficulty based on perceived difficulty. Post hoc analysis revealed the lowest performance for the hardest level. At a physiological level, the mean amplitude of the N1 ERP component was used to measure cognitive workload associated with the three difficulty levels. The N1 component’s amplitude decreased significantly (p<.001), with an increase in the task difficulty. Moreover, the amplitude of the N1 component for the hard level was significantly smaller compared to medium (p =.0003) and easy (p<.001) levels. These results support the utility of the N1 ERP component to measure cognitive workload in dynamic and real-life scenarios such as exergames and other rehabilitation exercises.